2020
DOI: 10.1021/acsanm.0c00263
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Isolation of Cancer-Derived Exosomes Using Fe/Au Magnetic Nanowires

Abstract: Isolating tumor exosomes (TEX) secreted by cancer cells can provide valuable information about the state of a tumor. Here, we present a method to rapidly isolate TEX using magnetic nanowires (MNWs). Specifically, two sets of Fe/Au segmented MNWs were used to isolate TEX released by canine osteosarcoma cell lines (OSCA 8,32,and 40). These MNWs were prepared by electrodeposition showcasing similar length (2.2(1) μm) and diameter (36(3) nm) but different Fe/Au segment thickness: 120(20)/30( 6) nm (sample A) and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 65 publications
3
37
0
Order By: Relevance
“…Advancement of nanotechnology has extensively expedited the emergence of novel magnetic nanostructures, such as magnetic nanowires (MNWs), in various research areas, including medical treatment [1][2][3][4][5], environmental science [6,7], and quantum devices [8][9][10][11][12]. These magnetic nanostructures have opened numerous opportunities for scientists in different disciplines such as nanomedicine, molecular biology [13][14][15][16], applied physics, and nanostructured materials [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Advancement of nanotechnology has extensively expedited the emergence of novel magnetic nanostructures, such as magnetic nanowires (MNWs), in various research areas, including medical treatment [1][2][3][4][5], environmental science [6,7], and quantum devices [8][9][10][11][12]. These magnetic nanostructures have opened numerous opportunities for scientists in different disciplines such as nanomedicine, molecular biology [13][14][15][16], applied physics, and nanostructured materials [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The special cylindrical geometry of MNWs gives rise to a well-dened magnetic anisotropy 16 that makes them suitable for many biological applications, such as MRI contrast, magnetic enrichment, and nanowarming. 11,[17][18][19][20][21] An external eld can be remotely used to physically excite MNWs, which makes them suitable for cell tracking, [22][23][24][25] cells manipulation, 26 cell separation, 27,28 drug delivery and drug activation, 29,30 magnetic hyperthermia, 21 and magneto-elastic ferrogels for tissue engineering. 31,32 Furthermore, the MNWs have shown a high internalization by cells in comparison to other magnetic nanoparticles, such as IONs, improving the enrichment and multiplexing yield.…”
Section: Introductionmentioning
confidence: 99%
“…In another example, Sharma et al observed high internalization of the gold-tipped nickel nanowires into osteosarcoma cells showing high cell activities and proliferation even after internalization of the magnetic nanowires [182,183]. In this direction, Nemati et al enriched canine osteosarcoma cells (OSCA 8, 32, and 40) using iron-gold multi-segmented nanowires and they successfully collected the cancer-derived exosomes with a yield competitive to the commercialized methods [4].…”
Section: Enrichmentmentioning
confidence: 99%
“…Advancement of nanotechnology has extensively expedited the emergence of novel magnetic nanostructures by reducing the dimensions to 2D nanomaterials, such as thin films and supperlattices, or 1D nanomaterials, such as magnetic nanowires (MNWs), and even 0D, such as spherical magnetic nanoparticles. The excellent quantum efficiency achieved using these nanomaterials has made them useful building blocks for diverse research areas, including medical treatment [1][2][3][4][5], environmental science [6,7], and quantum devices [8][9][10][11]. These magnetic nanostructures have opened numerous opportunities for scientists in different disciplines such as nanomedicine, molecular biology [12][13][14], applied physics, and nanostructured materials [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%